Implementation of Ambon Banana Consumption Education to Improve Family Ability in Caring for Family Members with Hypertension - Sintya Aprillianty Nurhalizah; Asep Riyana; Yanyan Bahtiar; Kusmiyati Kusmiyati (Asy-Syifa : Journal of Science and Technology Nursing, 2026)
Purpose: The purpose of this study was to describe the implementation of education on the consumption of Ambon bananas (Pisang Ambon) in improving family ability to care for members with hypertension in the Cikoneng Public Health Center area. Methods: This study used a case study design involving two families with hypertensive members. The intervention consisted of structured education delivered over five consecutive days using leaflet media and active family involvement in each session. The study focused on non-pharmacological management through dietary modification, particularly increasing potassium intake. Results: The results showed a significant improvement in family knowledge and attitudes regarding hypertension care after the educational intervention. Family characteristics such as the number of members, level of education, and occupation influenced the effectiveness of the education. Families with fewer members and higher education levels demonstrated faster understanding and better application of the information provided. Conclusions: Structured and continuous education on the consumption of potassium-rich foods such as Ambon bananas is effective in enhancing family capacity in hypertension management. It is recommended that similar educational programs be conducted routinely, considering family characteristics and involving health workers as facilitators to optimize outcomes.